Role of Naked Eye Single Tube Red Cell Osmotic Fragility Test (NESTROFT) in Detecting Beta-Thalassemia Trait - Ferdousi, Asma; Ahmad, Mainuddin; Sharma, Jhulan Das; Samad, Rasheda; Ullah, AKM Zafar (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Thalassemia is one of the commonest inherited diseases in Bangladesh. The birth of a thalassemic child places considerable strain, not only on the affected child and its family but also on the community and the nation at large. To reduce the burden of the society and to reduce the disease incidence by providing genetic counseling, detection of carrier is important. The present study evaluates the role of ‘Naked Eye Single Tube Red Cell Osmotic Fragility Test’ (NESTROFT) in detecting ß-thalassemia trait. The current study is a cross sectional study done during the period of September 2008 to August 2009. The study subjects were sibs, parents and relatives of thalassemia patients of age more than 1 year attending Pediatric department of Chittagong Medical College Hospital. Sample size was 50. Here subjects with lowered osmotic fragility test were detected and later on Hb- electrophoresis was done. All the data were recorded and analyzed by SPSS programme. The Sensitivity, Specificity and predictive value of positive and negative tests were computed and they were 92.6%, 80%, 92.6% and 80% respectively. False positive cases were found. The present study found NESTROFT to be both sensitive and reasonably specific and of high negative predictive value. However, multicenter study with large sample is needed to recommend NESTROFT as a single screening test for detection of ß-thalassemia trait. J Bangladesh Coll Phys Surg 2018; 36(4): 145-152